The Complexities and Challenges of Outsourcing Healthcare IT. (21st November 2022) - Madhavan, Naveen
Abstract: IT organisations at some point will have to consider whether to build or buy their services, writes Dr Naveen Madhavan MBCS, Senior Product Specialist (Pathology) at NHS Digital Health & Care Wales.